ANALISIS PARTISIPASI DAN PERSEPSI MASYARAKAT PETANI TERHADAP RESTORASI DAN PRESERVASI HUTAN - Ana Nurmalia; Wahyu Handono (Jurnal Agrisep)
Polemics on forest damage and socio-economic problems that arise then what can be done to balance management as an element of economic support but still do not forget the importance is to actively participate in saving by restoration and preservation of forests. Researchers are interested in conducting a more in-depth study of "community participation and perceptions of forest restoration and preservation with a case study in Lubuk Pinang Village, Lubuk Pinang District, Mukomuko District, Bengkulu Province. The research was done intentionally (purposive) using secondary and primary data from the interview process and the existing literature, the process of taking samples using the census method, and using descriptive analysis. The results of research showed community participation in forest restoration and preservation included in the high category of 26 , 27 and community perceptions of forest restoration and preservation are included in the high category of 24.17. In this study there is harmony between the level of perception and participation of both of them into the high category.